login
a(1)=1, a(n) = n*15^(n-1) + a(n-1).
1

%I #17 Feb 12 2024 06:36:14

%S 1,31,706,14206,267331,4823581,84557956,1451432956,24517448581,

%T 408951042331,6752105339206,110549175651706,1797251568229831,

%U 29043982525261081,466937872906120456,7473240118999870456

%N a(1)=1, a(n) = n*15^(n-1) + a(n-1).

%H <a href="/index/Rec#order_03">Index entries for linear recurrences with constant coefficients</a>, signature (31,-255,225).

%F G.f.: x/((1 - x)*(1 - 15*x)^2). - _Stefano Spezia_, Mar 11 2020

%o (PARI) a(n) = (1+15^n*(14*n-1))/196; \\ _Jinyuan Wang_, Mar 11 2020

%K nonn,easy

%O 1,2

%A _Olivier GĂ©rard_